Primary antibiotic resistance of helicobacter pylori strains isolated from Portuguese children: a prospective multicentre study over a 10 year period. - Oleastro, M (2011)
OBJECTIVES: The aim of this study was to prospectively assess the pattern of evolution of primary resistance to antibiotics in Helicobacter pylori strains isolated from Portuguese children over a 10 year period (2000-09). METHODS: A total of 1115 H. pylori strains were tested for antibiotic susceptibility to clarithromycin, metronidazole, amoxicillin, ciprofloxacin and tetracycline. RESULTS: H. pylori strains were isolated from children and adolescents [ages 4 months-18 years (mean age 10.17 ± 4.03 years)], comprising 562 (50.4%) boys and 553 (49.6%) girls. Overall, the primary resistance rate was 34.7% to clarithromycin, 13.9% to metronidazole and 4.6% to ciprofloxacin, while 6.9% were resistant to two of these antibiotics simultaneously. Resistance to amoxicillin and to tetracycline was not detected. In general, the resistance rate was not associated with gender or the children's age. European ethnicity, when compared with an African background, was associated with clarithromycin resistance [P = 0.002; odds ratio (OR) = 0.30; 95% confidence interval (CI) 0.14-0.66], while the inverse situation was observed for metronidazole (P < 0.001; OR = 3.50; 95% CI 1.90-6.45). No significant temporal trend was noticed for resistance to clarithromycin and metronidazole, whereas ciprofloxacin and double-resistance rates have significantly increased over time (P = 0.004 and P = 0.05, respectively). CONCLUSIONS: The primary resistance rate of H. pylori strains isolated from Portuguese children to the commonly used anti-H. pylori antibiotics used is high. Additionally, the increasing trend of ciprofloxacin-resistant and double-resistant strains may compromise H. pylori eradication in a high-prevalence population.